Habiter le Saint-Laurent. Présence du fleuve dans les dictionnaires faits au Québec de 1880 à aujourd’hui - Vincent, Nadine (Ponti/Ponts, 2021)
A dictionary is not just a list of words and definitions. It is also a witness of the culture and imagination of a society. To measure the place held by the St. Lawrence River in the reality and in the unconscious of Quebecers over the centuries, we have studied three dictionaries, those of Oscar Dunn and Sylva Clapin, of the 19th century, and the general dictionary Usito, of the 21st century, looking for the information given on the River itself, but also in search of the words with which it is associated, allowing us to discover the nerve center and symbolic role played by the St. Lawrence River in Quebec from 1880 to date.